Analysis of Science Literacy of XI Class Students In Buffer Solution Materials - Yudha, Sandy; Simorangkir, Murniaty; Nurfajriani, Nurfajriani (Universitas Negeri Padang, 2023)
The background of this research is that the world of education is currently intensively developing scientific literacy skills for students. This condition is the result of the rapid development of science and technology (IPTEK), so students must be able to act wisely and be able to adapt to science, environment, society, and technology. The purpose of this study was to determine the level of scientific literacy in nominal, functional, conceptual, and multidimensional aspects of class XI students on buffer solution material at State Senior High School (SMAN) 1 Binjai, Langkat Regency. This research method is a survey research, using a cross-sectional survey design. The sample in this study was taken from class XI IPA 1, totaling 30 people based on a purposive sampling technique. The research instrument used was a scientific literacy test in the form of essay questions, with indicators of scientific literacy referring to the theoretical framework. Based on the results of data analysis, it was found that the average value of students' scientific literacy abilities, nominal literacy indicators were 83.33%, functional indicators were 57.67%, conceptual indicators were 59.07%, and multidimensional indicators were 28.49%.